2015
DOI: 10.5603/fm.a2018.0016
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the feeding arteries of the cerebral arteriovenous malformations

Abstract: The knowledge of the origin and anatomic features of the AVMs feeders is important in the explanation of neurologic signs, and in a decision regarding the endovascular embolization, neurosurgical and radiosurgical treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(169 reference statements)
0
2
0
Order By: Relevance
“…Milatov's et al study of the anatomy of the feeding artery in arteriovenous malformations found that only 10.39% came from the posterior cerebral artery. 9 Yisen Zhan's study on imaging characteristics of arteriovenous malformations in the brain divided the blood supply from the posterior cerebral arteries to the nidus area into type I where the blood supply involves the posterior choroidal artery which is proximal to the posterior cerebral artery and type II involving the temporal and occipital branches originating distal to the posterior cerebral artery. Both of these branches have the same prevalence to supply blood to the nidus area.…”
Section: Discussionmentioning
confidence: 99%
“…Milatov's et al study of the anatomy of the feeding artery in arteriovenous malformations found that only 10.39% came from the posterior cerebral artery. 9 Yisen Zhan's study on imaging characteristics of arteriovenous malformations in the brain divided the blood supply from the posterior cerebral arteries to the nidus area into type I where the blood supply involves the posterior choroidal artery which is proximal to the posterior cerebral artery and type II involving the temporal and occipital branches originating distal to the posterior cerebral artery. Both of these branches have the same prevalence to supply blood to the nidus area.…”
Section: Discussionmentioning
confidence: 99%
“…BAVMs can occur in the supplying areas of different intracranial arteries, such as the anterior cerebral artery (ACA), posterior cerebral artery (PCA), and vertebrobasilar artery [2][3][4]. BAVMs can also occur in the supplying area of the middle cerebral artery (MCA), termed MCA-BAVMs, and they are unique due to the complex anatomy of the MCA [5].…”
Section: Introductionmentioning
confidence: 99%